Cluster 1 near the entrance of the temple complex - Temples of India Project Team (Jio Institute, 2024)
The Baroli group of temples are presently enclosed within a complex that has two clusters—the first is situated near the entrance, and the second at the backside of the complex. The image shows two temples from the first cluster which otherwise comprises three temples in total—two dedicated to Shiva and one to Sheshashayi Vishnu. The third temple is behind the Sheshashayi Vishnu Temple.